The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/jbc.m606086200
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Signal from ASJ Sensory Neurons Modulates Stomatin-dependent Coordination in Caenorhabditis elegans

Abstract: The neuronal stomatin-like proteins UNC-1 and UNC-24 play important roles in the nervous system of Caenorhabditis elegans. These neuronal stomatin-like proteins are putative chaperone proteins that can modify volatile anesthetic sensitivity and disrupt coordinated locomotion. A suppressor of unc-1 and unc-24, named ssu-1(fc73) (for suppressor of stomatin uncoordination), suppresses three phenotypes of neuronal stomatin-like protein deficiency as follows: volatile anesthetic sensitivity, uncoordinated locomotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 46 publications
5
46
0
Order By: Relevance
“…To date, only the genes trx-1 (thioredoxin-1) and ssu-1 (alcohol sulfotransferase-1) have been reported to be expressed exclusively in ASJ neurons (Carroll et al 2006;MirandaVizuete et al 2006). TRX-1 belongs to the thioredoxin family of redox proteins, playing a role in regulating worm longevity and dauer formation (Miranda-Vizuete et al 2006;FierroGonzalez et al 2011a,b).…”
mentioning
confidence: 99%
“…To date, only the genes trx-1 (thioredoxin-1) and ssu-1 (alcohol sulfotransferase-1) have been reported to be expressed exclusively in ASJ neurons (Carroll et al 2006;MirandaVizuete et al 2006). TRX-1 belongs to the thioredoxin family of redox proteins, playing a role in regulating worm longevity and dauer formation (Miranda-Vizuete et al 2006;FierroGonzalez et al 2011a,b).…”
mentioning
confidence: 99%
“…S3). This gene might be required in C. elegans for the biosynthesis of a secreted compound(s) involved in dauer formation and locomotion (Carroll et al, 2006). We also identified at least five genes with similarity to genes encoding heparan sulfate (HS) sulfotransferases in the C. elegans genome.…”
Section: Identification Of Genes Involved In Sulfation In C Elegansmentioning
confidence: 89%
“…Numerous essential genes have been identified on the left arm of chromosome V, and grouped into complementation groups by deficiency mapping and complementation tests (Johnsen and Baillie, 1991;Stewart et al, 1991). Using the cold-sensitive lethality, we (Carroll et al, 2006) Genes were identified by keyword search in GenBank, PFAM and re-iterative BLAST searches.…”
Section: Pst-1 Is Required For Kal-1-induced Axonal Branching and Mismentioning
confidence: 99%
“…The gene is highly expressed in embryos, growing larvae and in dauer larvae. Expression of SSU-1 in the ASJ neurons (amphid sensory neurons) was demonstrated and the protein showed sulfotransferase activity in vitro (28). This protein may modify endocrine signals in the worm.…”
Section: E Sulfotransferasementioning
confidence: 97%